Effects of Strength Training on Body Composition, Physical Performance, and Protein or Calcium Intake in Older People with Osteosarcopenia: A Meta-Analysis - Herrera-Valenzuela, T; Cid-Calfucura, I (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Objective: this systematic review with a meta-analysis aimed to evaluate the available body of published peer-reviewed randomized controlled trial (RCT) studies on the effects of different doses and types of strength training (ST) on body composition, physical performance, and protein or calcium intake in older people with osteosarcopenia. Method: a systematic literature search was conducted between July 2024 and August 2025 using five databases: PubMed, Medline, CINAHL Complete, Scopus, and Web of Science. PRISMA, TESTEX, RoB 2, and GRADE tools assessed methodological quality and certainty of evidence. Hedge s g effect sizes were calculated for the abovementioned variables for the meta-analysis. Results: the protocol was registered in PROSPERO (code: CRD42025643858). Of 141 registers, seven RCTs with 349 participants were included. Seven overall and two subgroup meta-analyses showed significant increases in skeletal muscle mass index (SMMI; p < 0.01), maximal isometric handgrip strength (MIHS; p = 0.03), and protein intake (p = 0.03). There were no significant differences in bone mineral density (BMD), body fat percentage (BFP), gait speed, and calcium intake. However, meta-analysis by subgroups showed significant decreases in BFP (p = 0.01) in favor of elastic band training versus resistance training, with no significant differences in BMD. Conclusions: ST in older people with osteosarcopenia conditions increases SMMI, MIHS, and protein intake.